Approaches to corporate debt restructuring in the wake of financial crises - Laryea, Thomas (IMF [Washington]US, 2010)
Discusses the economic case for moderated government intervention in debt restructuring in the nonfinancial corporate sector. Draws on lessons from past crises to explain three broad approaches that have been applied to corporate debt restructuring in the aftermath of a crisis. addresses challenges in designing and implementing a comprehensive debt restructuring strategy and draws together some key principles